Growth hormone gene family (GH, GHR, GHRH and Pit-1) polymorphisms and its association with superovulation response, ovulation rate and embryo quality in Embryo Transfer Station (BET) of Cipelang - Sumantri, Cece; Imron, M; ., Sugyono; Andreas, E.; Restu, M.; Ishak, A.B.L. (Indonesian Journal of Animal and Veterinary Sciences, 2011)
The decrease in fertility is considered to be the main cause of reproductive loss in dairy cattle and beef industry. Many candidate genes that play an important role in fertility and embryonic development. The purpose of this study was to detect genetic variations of the growth hormone gene family (GH|MspI, GH|AluI, GHR| AluI, GHRH|HaeIII and Pit-1|HinfI) and its association with superovulation response, ovulation, fertilization and transferable embryos rate. A total of 45 blood samples taken from cows that have been superovulated Angus, Brahman, HF, Limousin and Simmental. DNA was extracted with phenol-chloroform protocol followed by polymerase chain reaction technique (PCR) using specific primers for GH, GHR, GHRH and Pit-1 gene. PCR product was cut with restriction enzyme MspI, AluI, HaeIII and HinfI and electrophoresed on agarose gel and stained with ethidium bromide (EtBr). Superovulation is done by injecting a totally of 20 ml FSH for 4 days. Injecting the prostaglandin hormone (PGF2Î±) was performed on the eleventh day of CIDR implantation. Artificial insemination (AI) performed two or three days after the injection of PGF2Î± and Flushing was done on the seventh day after the AI. Â The results showed that the Angus, Limousin, Brahman and Simental GH loci diversity of GH|MspI, GH|AluI, GHR|AluI, GHRH|HaeIII and Pit-1|HinfI was not associated with superovulation response, ovulation, fertilization and transferable embryo rate. In HF dairy cattle, genotype on Pit-1|HinfI AA has higher percentage of superovulation response (P < 0.05) when compared to AB genotype, but did not differ to BB genotype. Dairy cattle HF AA genotype also had higher ovulation rate (P < 0.05) when compared to AB and BB genotypes, but AB and BB have the same ovulation rate. Key Words: Polymorphisms, Growth Hormone Genes and Reproduction traits.